The Speed of the Land: An Interview with Karen Jamieson - Gerecke, Alana (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2024)
Settler scholar and artist Alana Gerecke interviews settler choreographer Karen Jamieson about her decades-long career making site-based and community-engaged dances. In particular, Jamieson reflects on what she has learned about the complexities of orienting dance practice toward deepening connection with land, and of working with Indigenous collaborators in a respectful and non-extractive way.